Simulation-Based Analysis of Warehouse Layout to Enhance Material Handling Efficiency - Amalan, Yusuf Kurnia; Hartanti, Putri Felicia; Lin, David Weidong (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2025)
Warehouses play a critical role in modern supply chains, where inefficient layouts often lead to excessive travel distance, congestion, and high material handling costs. This study aims to analyze and improve warehouse layout performance using simulation-based approaches to enhance material handling efficiency. A comprehensive review of prior studies indicates that discrete-event simulation combined with systematic layout planning and storage assignment policies provides significant performance improvements in diverse warehouse contexts. This research adopts a simulation-based experimental design using FlexSim and Arena to evaluate alternative layout scenarios, incorporating dedicated, class-based, and shared storage strategies. Performance indicators include travel distance, material handling time, congestion level, and resource utilization. The results demonstrate that the proposed optimized layout reduces average travel distance by more than 35% and material handling time by up to 30% compared to the existing layout. These findings are consistent with previous studies reporting substantial efficiency gains through simulation-driven layout optimization. The study concludes that simulation-based warehouse layout analysis offers a robust decision-support tool for improving operational efficiency and provides practical insights for warehouse managers, particularly in small and medium-sized enterprises.